Search for new particles in an extended Higgs sector with four b quarks in the final state at s=13TeV - KAYA, MİTHAT (My University, 2022)
© 2022 The Author(s)A search for a massive resonance X decaying to a pair of spin-0 bosons ϕ that themselves decay to pairs of bottom quarks, is presented. The analysis is restricted to the mass ranges mϕ from 25 to 100 GeV and mX from 1 to 3 TeV. For these mass ranges, the decay products of each ϕ boson are expected to merge into a single large-radius jet. Jet substructure and flavor identification techniques are used to identify these jets. The search is based on CERN LHC proton-proton collision data at s=13TeV, collected with the CMS detector in 2016–2018, corresponding to an integrated luminosity of 138fb−1. Model-specific limits, where the two new particles arise from an extended Higgs sector, are set on the product of the production cross section and branching fraction for X→ϕϕ→(bb‾)(bb‾) as a function of the resonances\" masses, where both the X→ϕϕ and ϕ→bb‾ branching fractions are assumed to be 100%. These limits are the first of their kind on this process, ranging between 30 and 1 fb at 95% confidence level for the considered mass ranges.
Keywords: Fizik; Temel Bilimler; Physics; Natural Sciences; Temel Bilimler (SCI); FİZİK, NÜKLEER; Natural Sciences (SCI); PHYSICS; PHYSICS, NUCLEAR; Nükleer ve Yüksek Enerji Fiziği; Fizik Bilimleri; Nuclear and High Energy Physics; Physical Sciences; 2HDM; BSM; CMS; Higgs